2009
DOI: 10.1007/s11605-009-0963-y
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impact of Blood Transfusion on Recurrence and Prognosis of Hepatocellular Carcinoma After Hepatic Resection

Abstract: Transfusion of blood products is associated with increased recurrence rate and worse survival after elective hepatic resection for patients with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 61 publications
6
57
0
2
Order By: Relevance
“…Numerous studies reported that blood transfusion causes nonspecific immunosuppression, and affects postoperative complications and prognosis of HCC [25,26]. It is reported that blood transfusion is associated with increased incidence of HCC recurrence especially in early stages (I or II) and absence of vascular invasion [27]. In our study, perioperative blood transfusion was a significant predictor of tumour recurrence.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Numerous studies reported that blood transfusion causes nonspecific immunosuppression, and affects postoperative complications and prognosis of HCC [25,26]. It is reported that blood transfusion is associated with increased incidence of HCC recurrence especially in early stages (I or II) and absence of vascular invasion [27]. In our study, perioperative blood transfusion was a significant predictor of tumour recurrence.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, perioperative blood transfusion was a significant predictor of tumour recurrence. Several studies reported that perioperative blood transfusions are significantly associated with increased the incidence of tumour recurrence irrespective to its viral aetiology [13,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to clarify the predictor of HCC recurrence and prognosis for decision making in additional adjuvant treatment after hepatic resection, preoperatively. Several investigators have reported tumor size, vascular invasion, intrahepatic metastasis, tumor markers, excessive blood loss, and allogenic blood transfusion as factors associated with recurrence of HCC (4)(5)(6)(7). Unlike other solid malignancies, the prognosis of HCC is not solely dependent on tumor burden but also adversely influenced by impaired liver function secondary due to the underlying pathogenic condition (8).…”
Section: Introductionmentioning
confidence: 99%
“…Shiba et al (30) revealed an increased rate of pulmonary complications for patients who received blood products in hepatic resections for hepatocellular carcinoma. Additionally, early postoperative extubation seems to be associated with faster liver recovery after liver surgery.…”
Section: Discussionmentioning
confidence: 99%